Novel complexes of manganese(III), cobalt(II), copper(II), and zinc(II) with Schiff base derived from 1,2-bis(p-aminophenoxy)ethane and salicylaldehyde - Temel, H; Sekerci, M (Marcel Dekker Inc, 2001)
Several new complexes of the Schiff base obtained by the condensation of 1,2-bis(p-aminophenoxy)ethane with salicylaldehyde were synthesized. The complexes have been characterized by elemental analyses, magnetic measurements, H-1 NMR, UV-VIS and IR spectra. The ligand is coordinated to the central metal as a tetradentade ONNO ligand. The four bonding sites are the azomethine nitrogen and the o-OH groups.
Keywords: Nickel(Ii); Ligands; Ni(Ii); Cu(Ii); Co(Ii)